2017
DOI: 10.1016/j.jalz.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Free and Cued Selective Reminding Test – accuracy for the differential diagnosis of Alzheimer's and neurodegenerative diseases: A large‐scale biomarker‐characterized monocenter cohort study (ClinAD)

Abstract: Introduction: The International Working Group recommended the Free and Cued Selective Reminding Test (FCSRT) as a sensitive detector of the amnesic syndrome of the hippocampal type in typical Alzheimer's disease (AD). But does it differentiate AD from other neurodegenerative diseases? Methods: We assessed the FCSRT and cerebrospinal fluid (CSF) AD biomarkers in 992 cases. Experts, blinded to biomarker data, attributed in 650 cases a diagnosis of typical AD, frontotemporal dementia, posterior cortical atrophy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 41 publications
5
74
0
Order By: Relevance
“…However, the stronger and consistent relationship between both Aβ and tau and the memory composite is consonant with the hypothesis that episodic memory may be particularly vulnerable to early AD pathology. 44…”
Section: Discussionmentioning
confidence: 99%
“…However, the stronger and consistent relationship between both Aβ and tau and the memory composite is consonant with the hypothesis that episodic memory may be particularly vulnerable to early AD pathology. 44…”
Section: Discussionmentioning
confidence: 99%
“…In studies assessing memory performance in MCI in the general population, the FCSRT has shown to reflect hippocampalmediated consolidation memory defects better than free-list learning tests. Moreover, the FCSRT performance predicts progression to dementia in close relationship with progressive atrophy of the medial temporal lobe and other neocortical temporal and parietal regions (10,(14)(15)(16)(17)(18)(19). The FCSRT was administered using standard procedures as described by Grober and Buschke (20).…”
Section: Neuropsychological Assessment and Group Classificationmentioning
confidence: 99%
“…The identification of an ASHT should be used cautiously as a standalone diagnostic criterion given that abnormal FCSRT scores reflecting ASHT do not have an absolute specificity for typical AD. A recent large-scale cohort study including several neurodegenerative diseases has shown that a ASHT on the FCSRT has an excellent sensitivity (100%) for the detection of typical AD whereas its specificity is only of 75% [35]. A similar reasoning holds for HA which is correlated with the severity of ASHT [10].…”
Section: Discussionmentioning
confidence: 87%
“…In contrast to ASHT and HA, pathophysiological markers have a reliable sensitivity and specificity for detecting AD pathology at any stage of the disease. However, positivity of pathophysiological biomarkers without an ASHT excludes the diagnosis of typical amnesic AD and indicates the diagnosis of other neurodegenerative diseases which can be underpinned by AD pathology [35]. Such degenerative conditions linked to AD pathology have opened the AD spectrum to atypical AD variants, including cases of primary progressive aphasia, FTD, or posterior cortical atrophy.…”
Section: Discussionmentioning
confidence: 99%